Larval habitat characteristics of eastern eggar Eriogaster catax (Linnaeus, 1758) (Lepidoptera: Lasiocampidae) in Slovenia - Barbara Zakšek; Nika Kogovšek; Franc Rebeušek; Marijan Govedič (Natura Sloveniae)
The ecology of the eastern eggar (Eriogaster catax) in Slovenia has not been well characterized to date. Within the framework of this study, focusing on the larval habitat of the species, a total of 489 caterpillar webs found in different areas of Slovenia were recorded and a number of important variables documented. These included the host plant species, the size of the web, the height of the web from the ground, the height of the host plant, the trunk diameter at ground level, the web aspect and the general habitat characteristics. The most important host plants turned out to be blackthorn (Prunus spinosa) and hawthorn (Crataegus spp.), with one web found on Pyrus pyraster and one on Amelanchier ovalis. The web sizes varied largely, with the median size reaching 54 cm2. The position and height of the web from the ground was correlated with the height of the plant. Most caterpillar webs (67.4%) were oriented to the south, south-west or south-east. 61.5% of caterpillar webs were recorded in temperate heath and scrubs, with the majority of them found in sub-Mediterranean blackthorn-privet scrub (25.4%), followed by Atlantic and medio-European blackthorn-privet scrub (18.0%) and shrub woodland (13.1%). The present study provides the first insight into the ecology of the eastern eggar in Slovenia, focusing on larval habitat. The characterization of the larval habitat is of particular importance for the conservation of the eastern eggar and its potential habitat in Slovenia.